DEVELOPMENT STUDENT WORKSHEETS IN CLASS X PHYSICS BASED ON STATION-ROTATIONAL BLENDED LEARNING MODEL STATION-ROTATIONAL SKILL-ORIENTED RI 4.0 - rahmi juita husna; Pakhrur Razi (Universitas Negeri Padang, 2022)
The industrial revolution 4.0 is optimizing the use of digital technology to facilitate human work. The convenience offered is a challenge for humans, this can result in a reduction in the workforce because it has been replaced by robots (technology). This condition will be a challenge in the era of the Industrial Revolution 4.0. One of the important skills to be developed to answer these challenges is skill literacy. These literacy skills can be described as: data literacy, technology, and humans. The type of research that will be used in this research is research and development (Research and Development) with the object of research in the form of Student Worksheets (LKPD) which is oriented towards RI 4.0 literacy skills. The research will be carried out using the ADDIE research model which has the following steps: analysis, design, development, implementation, evaluation. The research results will be analyzed using descriptive analysis to analyze the data obtained. From the results of data analysis that has been carried out, it is found that the average value of the LKPD validation is 86.4, this value is in the very valid category. So it can be concluded that the LKPD is oriented towards literacy skills on Newton's Law and Work and Energy materials that are valid and can be used in the learning process in class X SMA. The research results will be analyzed using descriptive analysis to analyze the data obtained. From the results of data analysis that has been carried out, it is found that the average value of the LKPD validation is 86.4, this value is in the very valid category. So it can be concluded that the LKPD is oriented towards literacy skills on Newton's Law and Work and Energy materials that are valid and can be used in the learning process in class X SMA. The research results will be analyzed using descriptive analysis to analyze the data obtained. From the results of data analysis that has been carried out, it is found that the average value of the LKPD validation is 86.4, this value is in the very valid category. So it can be concluded that the LKPD is oriented towards literacy skills on Newton's Law and Work and Energy materials that are valid and can be used in the learning process in class X SMA.